2023
DOI: 10.1007/s40123-023-00744-7
|View full text |Cite
|
Sign up to set email alerts
|

Laser versus Anti-VEGF: A Paradigm Shift for Treatment-Warranted Retinopathy of Prematurity

Abstract: Retinopathy of prematurity (ROP), a leading cause of childhood blindness, has historically been associated with blindness from overgrowth of blood vessels from the retina into the vitreous that lead to complex retinal detachments. Our understanding of ROP has evolved with the survival of extremely low-birthweight infants and includes not only overgrowth of blood vessels, but also insufficient developmental retinal vascular growth in early phases of the disease. Our current treatments of ROP have focused on met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Advances in our understanding of retinopathy of prematurity (ROP) have improved its management and outcomes (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). However, additional research is needed, including our ability to predict those infants at greatest risk of blindness.…”
Section: Editorial On the Research Topic Identification Of Novel Biom...mentioning
confidence: 99%
See 1 more Smart Citation
“…Advances in our understanding of retinopathy of prematurity (ROP) have improved its management and outcomes (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). However, additional research is needed, including our ability to predict those infants at greatest risk of blindness.…”
Section: Editorial On the Research Topic Identification Of Novel Biom...mentioning
confidence: 99%
“…Several studies have pioneered ROP biomarker research in the blood of preterm infants. Many have focused on the role that vascular endothelial growth factor (VEGF) and insulinlike growth factor (IGF-1) play in neovascular development in the neonatal retina (5,11,(21)(22)(23)(24)(25)(26)(27)(28). More recently, advancements have been made in high-throughput omics techniques that allow the exploration of molecular profiles of metabolites, proteins, lipids, gene variants, and micro-RNA.…”
Section: Editorial On the Research Topic Identification Of Novel Biom...mentioning
confidence: 99%
“…The BEAT-ROP study 5 and the RAINBOW study 6 demonstrated the effectiveness of intravitreal injection of anti-VEGF agents in treating ROP. Recent years have witnessed a paradigm shift in the treatment of ROP from laser treatment to anti-VEGF injection 7 . Anti-VEGF injection offers several advantages over laser treatment such as eliminating the need for general anesthesia, providing a rapid clinical response, and permitting vascularization into the immature retina without causing permanent retinal damage 8 .…”
Section: Introductionmentioning
confidence: 99%